Contextualizing school achievement among vulnerable learners: Implications for science and practice: Commentary. Issue 183 (2nd May 2022) - Cutting, Laurie E.
ABSTRACT: The current set of papers in this special issue capture the range of viewpoints, scientific approaches, and populations needed to illuminate and tackle the issues of school achievement among vulnerable learners. This includes providing a framework for researchers to work from relevant policy findings, and literature reviews to small scale studies. The manuscripts also traverse different aspects of scientific inquiry – from data reported by federal and state programs, thus providing a "bird's eye view" of findings, to more granular neurobiological approaches. Across all papers is the clear theme of needing to shift from where we have been in order to establish a path forward for where we need to go to account for learners that have been relatively neglected in scientific studies. To break down barriers of inequity and increase our understanding of causes and consequences of vulnerable learners, there is a need to re‐think how we establish policies and allocate funds, as well as broadening our lens as we conduct scientific studies. Each piece in this special issue calls for the need to better understand these issues that vulnerable learners face to address inequities in our educational ecosystems. Together they provide a rich set of insights that have significant implications for science and practice.